DISTRIBUTION AND PREDICTION ON HEAVY METALS POLLUTION LEVEL (Pb, Cd, Cu, Zn, and Ni) IN SEDIMENT IN BANGKA ISLAND WATERS USING LOAD POLLUTION INDEX AND GEOACCUMULATION INDEX - Fasmi Ahmad (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Bangka Island is rich in natural resources particularly tin minerals. The increasing of tin mining has elevated various wastes such as tailings, oil, and fuel coming from the sand scraper tin boat. These wastes containing toxic heavy metals may harmful to marine organism. Measurement of Pb, Cd, Cu, Zn, and Ni were carried out in September 2010. The purpose of this research was to predict the pollution degree of Pb, Cd, Cu, Zn, and Ni in sediment using two different methods namely geoaccumulation index (I_geo) and pollution load index (PLI). The samples of sediments were collected at 20 stations using Gravity Core. The content of heavy metals in all samples was determined using Atomic Absorption Spectrophotometer with a mixture of air and acetylene flame. The results showed that there was a different of prediction on sediment pollution level between Load Pollution Index with Geoaccumulation Index. According to Load Pollution Index, sediments in this waters were not polluted by Pb, Cd, Cu, Zn, and Ni (PLI<1). Based on Geoaccumulation Index, sediment were also not polluted by Pb, Cu, Zn, and Ni (Igeo<0). While for Cd, sediments divided into three categories, namely not polluted (Igeo<0), light polluted (0<Igeo<1), and medium pollued (1<Igeo<2).  The concentration of the heavy metals still lower than that sediment quality guideline values. Keywords: Bangka Island, heavy metals, geoaccumulation index, pollution load index.